2010
DOI: 10.1890/08-1808.1
|View full text |Cite
|
Sign up to set email alerts
|

Topographic influences on vegetation mosaics and tree diversity in the Chihuahuan Desert Borderlands

Abstract: The abundance and distribution of species reflect how the niche requirements of species and the dynamics of populations interact with spatial and temporal variation in the environment. This study investigated the influence of geographical variation in environmental site conditions on tree dominance and diversity patterns in three topographically dissected mountain ranges in west Texas, USA, and northern Mexico. We measured tree abundance and basal area using a systematic sampling design across the forested are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
40
1
2

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 55 publications
1
40
1
2
Order By: Relevance
“…Piñon-juniper woodland is the dominant forest type which is comprised of Mexican piñon pine ( Pinus cembroides Zuccarini), alligator juniper ( Juniperus deppeana vonSteudal), gray oak ( Quercus grisea Liebmann), Graves oak ( Quercus gravesii Sudworth), Emory oak ( Q. emoryi Leibmann), and weeping juniper ( J. flaccida vonSchlechtendal) (Poulos & Camp, 2010). Lower elevations also contain small populations of one seed juniper ( J. monosperma Englemann) and red berry juniper ( J. pinchotii Sudworth) and oak shrublands that are dominated by Q. pungens Leibmann.…”
Section: Methodsmentioning
confidence: 99%
“…Piñon-juniper woodland is the dominant forest type which is comprised of Mexican piñon pine ( Pinus cembroides Zuccarini), alligator juniper ( Juniperus deppeana vonSteudal), gray oak ( Quercus grisea Liebmann), Graves oak ( Quercus gravesii Sudworth), Emory oak ( Q. emoryi Leibmann), and weeping juniper ( J. flaccida vonSchlechtendal) (Poulos & Camp, 2010). Lower elevations also contain small populations of one seed juniper ( J. monosperma Englemann) and red berry juniper ( J. pinchotii Sudworth) and oak shrublands that are dominated by Q. pungens Leibmann.…”
Section: Methodsmentioning
confidence: 99%
“…and an increase in topographic complexity would be expected to support a greater diversity of vegetation types (Radford et al 2005;Poulos and Camp 2010). Although intuitive, our finding is in contrast with those recent studies that have found the extent of habitat a stronger driver of woodland bird species richness as compared with environmental-(e.g.…”
Section: Landscape Heterogeneity Versus Extent Of Preferred Habitatcontrasting
confidence: 98%
“…This increased topographic complexity would be expected to support a greater diversity of microclimates, soil and vegetation types, which in turn provide a greater range of resources to be exploited Pineda and Halffter 2004;Radford et al 2005;Poulos and Camp 2010;Bishop et al 2014). Environmental heterogeneity associated with range in elevation has been shown to support greater diversity within numerous taxa, including frogs in Mexico (Pineda and Halffter 2004), and ants in South Africa (Bishop et al 2014).…”
Section: Different Responses At Different Scalesmentioning
confidence: 99%
“…Neste sentido, a abundância e a distribuição espacial das espécies nas comunidades vegetais podem ser reflexos das necessidades do seu nicho ecológi-co, além de reflexos das variações ambientais no tempo e espaço (Poulos & Camp 2010). Por outro lado, contrário às expectativas oriundas da teoria baseada em nicho, a teoria neutra prediz que a limitação de dispersão, especiação e o papel da estocasticidade ao longo do tempo podem levar espécies ecologicamente equivalentes a formarem padrões de distribuição e abundância similares àqueles observados na natureza (Hubbell 2001).…”
Section: Introductionunclassified